Analisis Faktor Penyebab Chronic Kidney Disease (N18) di Rumah Sakit Umum Kaliwates - Fi Isatir Rodiyah; Dony Setiawan Hendyca Putra; Ervina Rachmawati; Veronika Vestine (Indonesian Journal Publisher, 2024)
Chronic Kidney Disease (CKD) is one of the leading causes of death in indonesia with 2,221 deaths recorded in 2019. Kaliwates General Hospital located is one of the hospital in jember city that recorded an increase in chronic kidney disease cases from 2020 to 2022. The aims of this study is to identify the causative factors influencing the occurrence of chronic kidney disease based on inpatient medical records at Kaliwates General Hospital. The method used is a quantitative analytical approach with a case-control design. The research sample includes 79 cases of chronic kidney disease and 79 cases of urological disorders selected through purposive sampling. Data were analyzed using uniariat and bivariat approaches with chi-square test. The results of the bivariate analysis found a significant relationship between chronic kidney disease and several factors, including age (p value 0,005), hypertension (p value 0,001), diabetes mellitus (p value 0,002), and cardiovascular disease (p value 0,003). The hospital is expected to provide health education related to the causes of chronic kidney disease to patients, so that they can better understand the risk and take preventive actions to manage these risks.